The Role of Ultrasound, Scintigraphy, and Cytology in Evaluating Thyroid Nodules - Laçi, Ilirian; Spahiu, Alketa; Bodeci, Artan; Shpuza, Aldo (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract Background: Thyroid function testing and imaging studies guide the initial management of thyroid nodules. Our study aims to assess the role that ultrasound (US) and scintigraphy play in thyroid nodules. Methods: We conducted a prospective case series study of 212 consecutive patients presented with thyroid nodules at the tertiary University Hospital of Tirana (“Mother Teresa”) for further evaluation between January 2018 and March 2018. All patients were examined with US and scintigraphy with 99mTc and underwent fine- needle aspiration cytology. Generalized Linear Model (ordinal logistic) was used to predict the dependent variable with ’ordered’ multiple categories and independent variables. Results: The majority of patients (85%) were female, and (15%) males, p<0.001. The ordered logit for US finding’s presence of microcalcifications, adenopathy, solid or solidcystic nodules, being in a higher TIR category was 1.27, 4.56, 2.70 and 1.70 more than absence of microcalcifications, adenopathy and cystic nodules, respectively. Conversely, a one unit (year) increase in age would result in a 0.035 unit decrease in the ordered log-odds of being in a higher TIR category. For the scintigraphy findings, the ordered logit for isohypofunctional and hypofunctional nodules (vs. isofunctional), in a higher TIR category, was 1.70 and 2.10 higher, respectively. Conclusions: In thyroid glandular nodules, only a small percentage are malignant, therefore examination with ultrasound, scintigraphy and FNA are important to lower the number of patients undergoing surgery. Given the study’s results, scintigraphy has a significant value, but in order to diagnose malignant nodules ultrasound remained an initial and important diagnostic tool, which, when combined with FNA, rounds out a clear diagnosis of thyroid nodules.